2012
DOI: 10.1039/c2cs35028a
|View full text |Cite
|
Sign up to set email alerts
|

Tridentate ligands and beyond in group IV metal α-olefin homo-/co-polymerization catalysis

Abstract: The opening up of new markets, particularly in the Far East, is expected to increase the industrial demand for more (and new) plastic materials. In turn, this will drive the need for further catalyst development, with increased efficiency and with the capacity to easily control the resulting polymer properties being high on the agenda. With this in mind, tailoring the pre-catalyst structure has proved to be a very successful strategy, and has allowed for the elucidation of a number of structure-activity trends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
92
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(93 citation statements)
references
References 98 publications
0
92
0
1
Order By: Relevance
“…For this purpose, Cp N TiCl 3 (1e) appeared especially suitable to us, because its hemilabile Ndonor has been very useful in the organometallic chemistry of titanium complexes. [25,31] In this way, we performed the reductive complexation of imine 2e with 1e as the titanium precursor. Indeed, by this pathway, we were able to isolate the titanaaziridine 3f, which is distinguished by a further chlorido ligand in addition to the hemilabile Cp N ligand, in a yield of 68 % as a dark green solid (Scheme 7).…”
Section: Intramolecular-donor-stabilized Titanaaziridinesmentioning
confidence: 99%
“…For this purpose, Cp N TiCl 3 (1e) appeared especially suitable to us, because its hemilabile Ndonor has been very useful in the organometallic chemistry of titanium complexes. [25,31] In this way, we performed the reductive complexation of imine 2e with 1e as the titanium precursor. Indeed, by this pathway, we were able to isolate the titanaaziridine 3f, which is distinguished by a further chlorido ligand in addition to the hemilabile Cp N ligand, in a yield of 68 % as a dark green solid (Scheme 7).…”
Section: Intramolecular-donor-stabilized Titanaaziridinesmentioning
confidence: 99%
“…For examples, activities (TCD content) by [Et(Ind)2]ZrCl2 [32], [Ph2C(Ind)(Cp)]ZrCl2 [33], [Ph2C(Cp)(Flu)]ZrCl2 [33], [Me2C(3-MeC5H3)(Flu)]ZrCl2 [3], [Me2C(3-t BuC5H3)(Flu)]ZrCl2 [3] were 25 kg-polymer/mol-Zr•h (35 mol %), 31 (85 mol % at 90 °C), 24 (68), 1.3 (40), 0.4 (44), and respectively. Design of molecular catalysts for synthesis of new polymers with specified functions is one of the most attractive targets in the field of catalysis, polymer chemistry, and organometallic chemistry [37][38][39][40][41][42][43][44][45][46][47][48]. In this minireview, reported examples of copolymerization of COs (NBE, TCD) with olefins (ethylene, propylene, 1-hexene, 1-octene, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the NBE incorporation was lower than that obtained by complex A, especially at NBE concentration of 1.0 mol/L (2a: 33.8%, A: 53.2%, respectively). The resultant copolymers possessed relatively high molecular weights (MWs) with unimodal molecular weight distributions (MWDs), and the MW of the copolymers decreased upon the increasing NBE concentration (entries [1][2][3][4] …”
Section: Ethylene (Co)polymerization Catalyzed By 2a-cmentioning
confidence: 99%
“…The development of well-defined, single-site group 4 metal catalysts has attracted much attention for olefin polymerization [1][2][3]. Many studies have also been focused on the relationship between the structure and catalytic properties of a given catalyst with respect to polymer chain composition and architecture [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%